1998
DOI: 10.1021/jm960683m
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of m1-Selective Muscarinic Agonists:  (R)-(−)-(Z)-1-Azabicyclo[2.2.1]heptan-3-one, O-(3-(3‘-Methoxyphenyl)-2-propynyl)- oxime Maleate (CI-1017), a Functionally m1-Selective Muscarinic Agonist

Abstract: The synthesis and SAR of a series of (Z)-(+/-)-1-azabicyclo[2.2. 1]heptan-3-one, O-(3-aryl-2-propynyl)oximes are described. The biochemistry and pharmacology of 24Z (PD 142505) and its enantiomers are highlighted. 24Z is functionally an m1-selective muscarinic agonist. Efficacy and m1 selectivity reside in the R enantiomer, (R)-24Z (CI-1017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…However, they do not directly increase mAChR expression but increase the response of M4 receptors . Almost two decades ago, an experimental candidate CI‐1017 displayed improved spatial memory and exhibited dose‐limiting adverse effects only at efficacy level 100‐fold showing a possibility of improving cognition process related to cholinergic activity . The Merck candidate MK‐7622, an M1 muscarinic receptor agonist was halted prematurely at phase 2 trials with no reasons found over the literature review or the company's website .…”
Section: Muscarinic and Nicotinic Acetylcholine Receptors Agonist Andmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they do not directly increase mAChR expression but increase the response of M4 receptors . Almost two decades ago, an experimental candidate CI‐1017 displayed improved spatial memory and exhibited dose‐limiting adverse effects only at efficacy level 100‐fold showing a possibility of improving cognition process related to cholinergic activity . The Merck candidate MK‐7622, an M1 muscarinic receptor agonist was halted prematurely at phase 2 trials with no reasons found over the literature review or the company's website .…”
Section: Muscarinic and Nicotinic Acetylcholine Receptors Agonist Andmentioning
confidence: 99%
“…[28] Almost two decades ago, an experimental candidate CI-1017 displayed improved spatial memory and exhibited dose-limiting adverse effects only at efficacy level 100-fold showing a possibility of improving cognition process related to cholinergic activity. [29] The Merck candidate MK-7622, an M1 muscarinic receptor agonist was halted prematurely at phase 2 trials with no reasons found over the literature review or the company's website. [30][31][32] Nicotinic receptors (nAChRs) also respond physiologically to ACh, and the a7 and a4b2 subtype expressing neurons are particularly found to be damaged in patients suffering from AD.…”
Section: Muscarinic and Nicotinic Acetylcholine Receptors Agonist Andmentioning
confidence: 99%
“…The final step to achieve the N-O-substituted a-amino b-methyl b-lactam analogues started from 18 which was either submitted to a classic Mitsunobu reaction [24,25] with various alcohols to obtain the N-O-alkyl derivatives (19e29), or to a copper catalyzed coupling reaction [26] with arylboronic acids to afford the corresponding N-O-aryl b-lactams (30e39) (Scheme 2).…”
Section: Chemistrymentioning
confidence: 99%
“…11.7. 4-Cyclohexylbutyl-((2S,3S)-2-methyl-1-(3-(methylsulfonyl) propoxy)-4-oxoazetidin-3-yl)carbamate(25). The reaction was carried out following the general procedure GP1 employing 18 (0.1 g, 0.33 mmol), triphenylphosphine (0.104 g, 0.40 mmol), 3-(methylsulfonyl)propan-1-ol (0.055 mL, 0.40 mmol) and DEAD (0.175 mL, 0.40 mmol).…”
mentioning
confidence: 99%
“…CI-1017 is a second generation agonist designed to selectively activate the M1 receptor while minimizing peripheral side effects (Tecle et al, 1998). It is an oxime of 1-azabicyclo[2.2.1] heptan-3-one with a 3-phenylpropargyl analog substituent, and it is identified as a relatively m1-selective partial agonist by cell metabolism, cell amplification, and second messenger assays with an overall selectivity of m1 Ն m4 Ͼm3 ϭ m5 Ͼ Ͼ m2 (Jaen et al, 1995).…”
mentioning
confidence: 99%